Predictors of nurses' work-related mental health during the COVID-19 pandemic: a paired follow-up study - Nagel, Cicilia; Nilsson, Kerstin (Frontiers in Health Services, 2025)
Nurses are essential pillars of society, providing care for the sick. It is crucial for society to ensure that nurses have favorable working conditions, as they face a heightened risk of negative psychological conditions such as depression, anxiety, stress, and emotional exhaustion due to the demanding nature of their work. The strain on healthcare staff, particularly during the COVID-19 pandemic, has underscored these challenges. This study aimed to identify predictors of work-related mental health issues in nurses' work environments. In 2017, a questionnaire was distributed to 9,219 Swedish nurses, with 4,962 responses received. The questionnaire was redistributed during the pandemic in 2020, and 3,107 nurses responded. However, due to missing data and some nurses previously reporting a mental health diagnosis, only 2,030 questionnaires were included in the study. Among these, 143 nurses reported experiencing work-related mental health problems. The data was analyzed by logistic regression analysis, and 6 out of the 24 statements investigated were statistically significant (p < 0.05), i.e., there was a longitudinal association between nurses’ work situation and their mental health problems. The six statements were “I do not feel I get enough rest/recuperation between work shifts”, “The work pace in my daily work is too high”, “I do not feel I have enough support from my coworkers”, “I do not experience joy in my daily work”, “I do not feel like my daily work is meaningful”, and “I do not get enough opportunities at work to utilize my skills and knowledge”.ConclusionsThis study revealed that work pace, recovery, support from colleagues, joy, meaningfulness, and development opportunities at work are particularly important for nurses' mental health. Actions in those areas are needed for nurses to have a sustainable work situation.